Social Network Analysis applied to Marvel Crisis Protocol - Silva, Igor Magno; Contreras, Rodrigo Colnago (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2025: Anais do XXIV Simpósio Brasileiro de Jogos e Entretenimento DigitalDO - 10.5753/sbgames.2025.8002, 2025)
Introduction: Social Network Analysis (SNA) based on Graph Theory has proven to be a powerful tool for modeling and understanding interactions in various contexts. In this study, we apply SNA to examine the connections and synergies between characters in the Marvel Crisis Protocol (MCP) miniatures game, a tabletop miniatures game where players form teams of Marvel heroes and villains based on abilities, affiliations, and strategic synergies. Objective: This study aims to analyze the undefeated lists of the tournaments in the first quarter of 2025 and verify if there is any competitive advantage in using the most influential characters according to the centrality measures of Graph Theory. Methodology or Steps: For this purpose, a simulation of a Social Network Analysis was carried out using the characters’ Affiliations as a basis using five centrality measures. Results: After identifying the influential characters, a comparison was made with the undefeated lists to verify whether such characters make up the winning rosters and if using a team with two Affiliations is a good strategy. Unfortunately, single Affiliations roosters performed better in the championships analyzed.